Audit Sistem Informasi Perpustakaan Sekolah Menggunakan Frame Work Cobit 5 Pada SMAN 1 Terbanggi Besar Lampung Tengah - Danianty Miranda Br. Bangun; Maida Andriani; Risdiana Risdiana (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
The impact of standardization on Labor Vocational High School (SMK Labor) is felt by students, teachers, and staff, particularly in all activities related to the library information system that must comply with the procedures (SOP) established in ISO 9001:2000 SOP. The current library information system has not been audited yet, and it is not known whether it has supported the achievement of the school's vision and mission. A technique is needed to control and ensure that the library information system aligns with the organization's objectives. This is the reason why an audit of the Library Information System usage at SMAN 1 Terbanggi Besar needs to be conducted. The audit of the library information system uses the COBIT 5 framework with the Delivery, Service, and Support (DSS) domain, namely DSS.1, DSS.5, DSS.11, DSS.12, and DSS.13. The research results show that there is one process with capability level 4, which is DSS02, and there are five processes with capability level 3, namely DSS01, DSS03, DSS04, and DSS05. The overall capability level obtained based on the average is 3, which means that most of the activities in the DSS domain for the library information system at SMAN 1 Terbanggi Besar have been carried out. There are standardized implementations for these processes, and they are well-documented and communicated. This study implies that through the assessment of capability levels related to the Library Information System at SMAN 1 Terbanggi Besar, it can be continued in the future development of specific business processes, especially when there is an increasing number of customer services with diverse library service products. This can be done within the COBIT 5 audit framework.